2019
DOI: 10.1097/pcc.0000000000002078
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Difficulties Questionnaire Assessment of Long-Term Psychological Outcome in Children After Intensive Care Admission*

Abstract: Objectives: We investigated the long-term psychologic symptoms of patients who survived pediatric intensive care admission. Design: Longitudinal follow-up study. Setting: Nationwide cohort study based on a national ICU register and a questionnaire survey. Patients: All pediatric patients (0–16 yr old) who were admitted to an ICU in Finland in 2009–2010. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Our search strategy identified 9193 records. Of those, 205 full-text articles were assessed for eligibility, and 43 articles consisting of 31 independent studies involving 7786 children admitted to the PICU were included in the systematic review (Figure 1). Of the 31 independent studies, 5 were RCTs, 13 were prospective cohort studies, 10 were retrospective cohort studies, 1 was a case-control study, and 2 were cross-sectional studies .…”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy identified 9193 records. Of those, 205 full-text articles were assessed for eligibility, and 43 articles consisting of 31 independent studies involving 7786 children admitted to the PICU were included in the systematic review (Figure 1). Of the 31 independent studies, 5 were RCTs, 13 were prospective cohort studies, 10 were retrospective cohort studies, 1 was a case-control study, and 2 were cross-sectional studies .…”
Section: Resultsmentioning
confidence: 99%
“…Since the concept of positive psychological capital was put forward, it has been favored by psychologists and management scientists. Currently, the measurement questionnaire of positive psychological capital research mainly consists of one dimension, three-dimension, four-dimension, and multi-dimension theories ( Kyösti et al, 2019 ). Table 1 shows the corresponding structure and scale of positive psychological capital.…”
Section: Methodsmentioning
confidence: 99%
“…This study addresses cross-informant invariance in the SDQ ( Goodman, 1997 , 2001 ): one of the most widely used measures of child mental health globally. In pediatric contexts, it has been suggested that the SDQ can be used to increase the identification of mental health issues when used as a screen in primary care ( Brown & Wissow, 2010 ) and to monitor outcomes for children whose medical history puts them at elevated risk of social, emotional, and behavioral problems ( Bartal et al, 2020 ; Kyösti et al, 2019 ; Martinos et al, 2018 ). The instrument has five subscales measuring conduct problems, ADHD symptoms, emotional problems, peer problems, and prosociality.…”
Section: Introductionmentioning
confidence: 99%